Pengembangan Bahan Ajar SKI Berbasis ICT dalam Peningkatan Ketuntasan Belajar Siswa di MIN 2 Banda Aceh - Kartika Devi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The use of ICT-based teaching materials in learning is very influential in increasing student learning mastery. Learning media is now more dominant using only guides books and this will make students bored in learning, especially history lessons will make students less fond of the lesson because the selected media is not appropriate. This study aims to determine the validity of ICT-based SKI teaching materials in increasing student learning mastery at MIN 2 Banda Aceh, teacher and student responses to the development of ICT-based SKI teaching materials in increasing student learning mastery at MIN 2 Banda Aceh, and student scores after applying teaching materials. ICT based on SKI lessons at MIN 2 Banda Aceh. The research method used in this thesis is R&D (research and development) using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques through validation sheets, questionnaires, and tests. The results showed that ICT-based teaching materials in SKI lessons in the form of e-modules got a good score from the validity of material and media experts, namely 88.75%. The result of the teacher's response got a score of 89.5, and the average percentage of the student's response got a score of 87%. The learning outcomes obtained by students after conducting formative tests were an average of 87 in the small group, and 86.7 in the large group. The average value exceeds the predetermined KKM, which is 75. Thus, it can be concluded that the e-module material on the Hijrah of the Prophet Muhammad allallahu 'Alaihi Wasallam to Taif and also other materials deserve to be distributed.